Elementary School Physical Education Teachers' Perceptions of Strengthening Character Education in Physical Education - Isyabella, Annisa; Suherman, Ayi; Supriyadi, Tedi (Mimbar Sekolah Dasar, 2024)
The government has been implementing the Strengthening Character Education (PPK) program since 2016, mandating teachers, including Physical Education (PE) teachers, to integrate character values into the learning process. However, practical implementation often needs to be improved, with character values being documented mainly in administrative records like learning plans. Preliminary studies in the Sumedang district reveal a need for more emphasis on the affective domain, as PE teachers tend to focus on the psychomotor domain. So, in-depth research must be conducted on this topic. This research, a case study involving 10 PE teachers in Sumedang Regency, explores their perceptions of character education. The data were collected by distributing short questionnaires to collect participant demographic data; ten people participated in semi-structured interviews. Through inductive and thematic data analysis, themes voiced by participants were identified, evaluated, and created with the help of NVivo 12 Pro. Significant findings emerged through open questionnaires and semi-structured interviews, which included teacher understanding, urgency, challenges, learning strategies in integrating character values, and PPK's contribution to improving holistic student development. This research contributes to improving the quality of physical education learning in elementary schools, which is oriented toward strengthening character education. These insights are crucial for policymakers, curriculum writers, and educators to enhance character education in physical learning.